OPTIMASI PRODUKSI DAUN DAN SINENSETIN TANAMAN KUMIS KUCING (Orthosiphon aristatus Benth.) PADA BERAGAM INTENSITAS CAHAYA DAN TAKARAN NPK DI INCEPTISOL, KALITIRTO, SLEMAN - , NUR AFNI AFRIANTI ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aimed to study the effect of variation of light intensity and NPK fertilizer dosage to leaves production and sinensetin content of Java Tea (Orthosiphon aristatus Benth.) leaves on Inceptisol, Kalitirto, Sleman. The field research was arranged in a split plot design with three replications. The main plots was levels of sunlight shading (N0 = without shading